ADMINISTRATIVE STRESS AND ITS RELATION TO JOB SATISFACTION AMONG ADMINISTRATIVE BODIES IN SPORTS CLUBS PARTICIPATING IN THE PREMIER LEAGUE FOOTBALL IN IRAQ - Shakir, Salah Wahab (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to (1) assess the level of administrative stress and job satisfaction of the administrative bodies in the clubs participating in the Premier League football clubs in Iraq for the 2017/2018 season, and the relationship between them, (2)develop two questionnaires to measure both administrative stress and job satisfaction in these administrative bodies. The researcher through which can achieve the objective results and the study objectives. A descriptive survey was used in this study on a sample of (190) members of the administrative bodies who were selected purposively from the boundaries of the society of origin represented by the administrations of the Premier League football clubs for the sports season (2017-2018) and by 100%. The stress management questionnaire included four factors: organizational work stressor, internal and external environment stressors, situational stressors, and expectations stressors. The job satisfaction measure includes four factors as well: administrative and financial policies, leadership performance, self-realization and performance evaluation; and the organizational climate. Each factor of the questionnaires included seven items to be a total of (28) items for each scale.